2022
DOI: 10.2991/ahsr.k.220108.002
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Clusters in Malaysia

Abstract: Understanding COVID 19 cluster infection is vital as it evaluates the current situation and serves as the basis of further action in control and prevention strategies. We aim to describe the characteristics of COVID-19 clusters in Malaysia based on location, types, positive percentage, and case fatality ratio (CFR). We used open-source data of COVID-19 clusters from the GitHub Ministry of Health Malaysia website. The data were downloaded, cleaned, and analysed using SPSS version 27. The analysis includes data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
1
5
0
Order By: Relevance
“…Besides, 6175 out of 7328 (or 84%) locations visited by COVID-19 patients in our extracted dataset fall under category of workplace and this is clearly depicted in Figure 6(a). This agrees with the finding that the workplace clusters represent the highest percentage of all clusters in Malaysia [28] and disease prevention measures have to be targeted on high-risk areas such as the workplace. It is also worth mentioning that the exposed locations listed under a division might go beyond the administrative boundary of that division, as depicted by several points outside Kuching Division in Figure 6(a).…”
Section: Results Of Geospatial Statistical Analysissupporting
confidence: 90%
“…Besides, 6175 out of 7328 (or 84%) locations visited by COVID-19 patients in our extracted dataset fall under category of workplace and this is clearly depicted in Figure 6(a). This agrees with the finding that the workplace clusters represent the highest percentage of all clusters in Malaysia [28] and disease prevention measures have to be targeted on high-risk areas such as the workplace. It is also worth mentioning that the exposed locations listed under a division might go beyond the administrative boundary of that division, as depicted by several points outside Kuching Division in Figure 6(a).…”
Section: Results Of Geospatial Statistical Analysissupporting
confidence: 90%
“…The isolated conditions in custodial settings may also explain the relatively higher test positivity rate among clusters in these settings, as all suspected cases within the settings were screened. ( 11 ) Malaysia implemented several mitigation measures to reduce and contain the spread of COVID-19 within custodial settings, including setting up temporary detention centres, treatment centres in prisons and makeshift hospitals. ( 24 ) All new inmates were screened and isolated, if necessary, before being transferred to a permanent cell.…”
Section: Discussionmentioning
confidence: 99%
“…This is because comorbidities increase the risk of complications and death. 11 The analysis of detection methods showed that targeted screening was the most common detection method for custodial settings, and imported and workplace clusters. Symptomatic screening was the predominant method used for detecting cases in the community, in educational institutions and among high-risk groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selangor was the state most affected by the COVID-19 pandemic. According to the number of new COVID-19 cases reported daily by the Ministry of Health (MOH) for the months of January and February 2022, Selangor was the state with the highest number of new cases (17,18). By December 2022, Selangor still had the third highest number of COVID-19 cases per 1000 people (19).…”
Section: Study Setting and Samplementioning
confidence: 99%